Developing best practice guidelines on equine colic. (10th January 2015) - Freeman, S. L.; Curtis, L.
Abstract : Sarah Freeman and Laila Curtis describe an ongoing project that is aiming to develop evidence‐based, best practice guidelines to help owners and veterinary surgeons recognise the signs of colic in horses. They also report on the first of two multidisciplinary workshops during which the evidence was discussed by a range of different stakeholders